SCIENTIFIC HYPOTHESIS “VARIETY AND POPULATION IN AGROBIOCENOSIS OF POTATOES” - Ergashev, I.T.; Begimkulov, I.B.; J., Razzokov; F., Oblokulov (International Journal of Psychosocial Rehabilitation, 2020)
The results of studies on the formation of agrobiocenosis of potatoes, based on the study of the biological characteristics of some varieties, soil and climatic conditions, and crop cultivation technology, are presented. The scientific hypothesis about the likelihood of the formation of new strains of pathogens when combining biocenoses is also substantiated.It was discussed on formation of agrobiocenoses, based on biological pecualirities of varieties of potato, soil- climatic conditions and production technology of crop. It was Scientifically prouved hopoteses on relativity of formation of new strains, cousing different problems at mixed biocenoses.